Adamantanes Enhance the Photovoltaic Performance and Operational Stability of Perovskite Solar Cells by Effective Mitigation of Interfacial Defect States. Issue 19 (3rd April 2018) - Tavakoli, Mohammad Mahdi; Bi, Dongqin; Pan, Linfeng; Hagfeldt, Anders; Zakeeruddin, Shaik Mohammed; Grätzel, Michael
Abstract: Passivation of electronic defects is an effective strategy to boost the performance and operational stability of perovskite solar cells (PSCs). Identifying molecular materials that achieve this purpose is a key target of current research efforts. Here, adamantane (AD) and 1‐adamantylamine (ADA) are introduced as molecular modulators to abate electronic defects present within the bulk and at the perovskite–hole conductor interface. To this effect, the modulator is added either into the antisolvent (AS) to precipitate it together with the perovskite (AS method) or they are spin coated (SC) onto its surface (SC method). Time‐resolved photoluminescence measurements show substantially longer lifetimes for perovskite films treated with AD and ADA compared to the reference sample. In line with this observation, it is found that the presence of AD and ADA molecules at the interface between the perovskite film and the hole conductor increases all photovoltaic metrics, in particular the open circuit photovoltage ( V oc ) as well as the operational stability of the PSC. Abstract : The introduction of adamantane modulators as an interfacial layer between the perovskite and hole transporting layer enhances the photovoltaic performance and operational stability of state‐of‐the‐art perovskite solar cells by effective mitigation of interfacial defect states.